The effect of Climate Finance on Greenhouse Gas Emission: A Quantile Regression Approach - Carfora, Alfonso; Ronghi, Monica; Scandurra, Giuseppe (International Journal of Energy Economics and Policy, 2017)
Climate finance plays a primary role in international climate change agreements. It is a way to involve flows of funds from developed to developing countries that aims to help poorer countries shift toward low-emission, climate-resilient development pathways. In this paper, we study the flow of funds intended to promote energy generation and supply and biosphere protection in order to identify preferential channels in “Fast-start finance” distribution. We analyze the flow of funds among countries and the relationship between climate finance and a composite indicators that summarize and rank the greenhouse gas emissions by using a quantile regression model. Our results revealed a strong heterogeneity in the way the funds are being allocated by donors and show that close attention should be paid to the analysis of political contexts. Keywords: climate funds; composite indicator; developing countries. JEL Classifications: C31; Q48